(untitled) (INNOVATIVE ECONOMY, 2020)
Brechko O.V., Vorobets V.E. INSTITUTIONAL, ORGANIZATIONAL AND ECONOMIC DETERMINANTS OF THE USE OF BLOCK CHAIN TECHNOLOGIES IN THE FINANCIAL SECTOR Purpose. The aim of the article is substantiation of organizational, economic and institutional determinants of the use of block chain technologies to solve problems in financial transactions and significantly reduce of financial risks. Methodology of research. The methodological basis of the study is the dialectical method of scientific knowledge. General and special methods are used in the process of research, in particular: system approach ‒ in studying the connections between phenomena and processes in the system of ensuring the effective development of block chain technologies; deductive ‒ in the study of problems of block chain technologies in the financial sector, a comparative approach ‒ to compare and structure block chain technologies; graphic ‒ for visual and schematic display of theoretical and practical results of research; abstract and logical ‒ in carrying out theoretical generalizations, forming conclusions. Findings. It has been determined that block chain technologies are related to the computerization of payment systems. It has been proven that block chain or distributed ledger technology (DLT) introduces a system of decentralized payment systems, with cryptographic methods of encrypting information. The spread of the use of the latest digital technologies in the system of the global financial space is substantiated. The role of block chain technologies as a strategic resource of competitive positioning of national economies is noted. Originality. The support of the venture capital market is substantiated through separate measures. It is proposed to consolidate the requirements for venture investors at the legislative level. The theoretical substantiation of the use of block chain technologies is further developed. Practical value. The results of the study can be used in the latest digital technologies: in lending P2P (Peer-to-Peer); public governance; dispute resolution, order management, product promotion; accounting. The use of block chain technologies will significantly reduce the time for banking and real-time payments. Key words: digital agenda, digital services, digital technologies, block chain, digital assets, institutional basis of digitalization, financial sector.